IMPLEMENTATION OF THE MERDEKA CURRICULUM IN IMPROVING THE QUALITY OF EDUCATION AT STATE VOCATIONAL HIGH SCHOOL 4 TEBING TINGGI - Sinaga, Roni; Siti Salmaniah, Nina; Arif Nasution, Muhammad (Pena Cendekia Insani, 2026)
The implementation of the Merdeka Curriculum is a strategic government policy aimed at improving the quality of education, particularly vocational education that is oriented toward graduates’ work readiness. This study aims to analyze the implementation of the Merdeka Curriculum at Vocational High School 4 Tebing Tinggi in improving the quality of education, as well as to identify the inhibiting factors in its implementation. This research employs a qualitative approach with a descriptive method. Data collection techniques include observation, in-depth interviews, and documentation. The research informants consist of the principal, vice principals, teachers, and students of Vocational High School 4 Tebing Tingg. The results show that administratively, the Merdeka Curriculum has been implemented at Vocational High School 4 Tebing Tinggi; however, its implementation has not yet been optimal. This is indicated by the continued dominance of conventional learning patterns, teachers’ limited understanding of project-based learning, and students’ lack of understanding of the objectives and mechanisms of the Merdeka Curriculum. The inhibiting factors in the implementation of the Merdeka Curriculum include ineffective policy communication, limitations in human resources and facilities, as well as uneven readiness among policy implementers.